Divergent sucker-corm endophytic microbiota underpins the progressive decline of Fusarium-wilt incidence in resistant bananas across ratoon cycles - Xiang, Sainan; Tian, Dandan; Chen, Jiahui; He, Zhangfei; Wei, Liping; Qin, Liuyan; Li, Chaosheng; Li, Baoshen (Frontiers in Microbiology, 2026)
Fusarium wilt of banana, caused by Fusarium oxysporum f. sp. cubense (Foc), threatens global banana production. Resistant cultivars exhibit reduced disease incidence after successive ratoon cycles, but the underlying micro-ecological mechanisms remain unclear. This study represents the first longitudinal analysis of corm endophytic microbiota across ratoon cycles in banana, revealing temporal dynamics that underpin progressive disease resistance. A three-cycle field trial with three biological replicates per cultivar per cycle was conducted in a Foc-infested orchard in Guangxi, China. Corm tissues were sampled from resistant (‘Bao Dao Jiao’ and ‘Gui Jiao 9’) and susceptible ‘Williams B6’ bananas (n = 3 biological replicates per group) at plant crop (cycle 1) and third ratoon (cycle 3). 16S rRNA amplicons were sequenced via Illumina NovaSeq. Alpha- and beta-diversity, taxonomic composition, and predicted functions (PICRUSt2) were analyzed. Resistant cultivars maintained significantly higher Chao1 and Shannon indices than the susceptible cultivar, with divergence intensified across ratoon cycles (p < 0.05). Community structure was shaped primarily by cultivar rather than maternal health status. Resistant genotypes enriched Proteobacteria and Actinobacteria, alongside beneficial genera (Halomonas, Nesterenkonia, Aliihoeflea). Functional predictions revealed enrichment in carbohydrate metabolism, membrane transport, and xenobiotic degradation pathways in resistant cultivars. Disease incidence declined significantly from 34–39% (cycle 1) to 4–8% (cycle 3) in resistant cultivars, whereas susceptible cultivars remained at 44–59%. Resistant bananas continuously recruit beneficial endophytes during ratooning, assembling a stable microbiome that reinforces Fusarium wilt resistance. These findings provide microbial targets for breeding and biocontrol strategies.